KSZTAŁTOWANIE KOMPETENCJI PRZEDSIĘBIORCZOŚCI U UCZĄCYCH SIĘ METODĄ PROJEKTU Z WYKORZYSTANIEM TECHNOLOGII INFORMACYJNO-KOMUNIKACYJNYCH NA LEKCJI JĘZYKA OBCEGO - Posiadała, Katarzyna (Neofilolog, 2018)
This article is devoted to the value and role of the project method with the use of information and communications technologies in the development of entrepreneurship competence in foreign language learning. In the first part of the paper the author defines several meanings of entrepreneurship, focusing mainly on definitions of personal entrepreneurship. The article points out that the project method creates the conditions under which students develop an entrepreneurial attitude, learn group interaction and acquire communication skills, which are important for the socialization of adolescent students. The main purpose of project method is to turn a foreign language from a passive object into an active action. Particular attention is paid to the stages of the project with the use of the information and communications technology in foreign language learning.